La biographie d’objet : une écriture et une méthode critique - Thierry Bonnot; Bérénice Gaillemin; Élise Lehoux (Images Re-Vues)
Biographical method applied to material objects is introduced by Igor Kopytoff in his paper, “The cultural biography of things,” published in 1986. Such method arguably can be used with relevance in contemporary critical thought, with caution against falling into what Pierre Bourdieu terms “biographical illusion” (1987). Drawing on myriad prior and current case studies, this interview aims to define the biography of object as a critical enquiry method, not only consisting of an artificial or “ideal typical” story, but also as applied to real situations, involving actual objects and researcher himself, with emphasis on turning points, failures, changes, and career bifurcations of the objects. As a necessarily interdisciplinary method, the biographical method engages anthropology, history and archaeology, bringing biographically singularity and agency of objects into context. As a writing method of material culture’s social sciences, the biographical method possesses a strong heuristic capacity.